Research on generative sign language using neural networks - Selim, Bushra Binte; Iqbal, Maliha; Shahriar, Asif; Faria, Fauzia; Mostafa, Rafid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.